Dendritic cell vaccine of gliomas: challenges from bench to bed - Zheng, Ye; Ma, Xiaoyu; Feng, Shouchang; Zhu, Hongtao; Chen, Xin; Yu, Xingjiang; Shu, Kai; Zhang, Suojun (Frontiers in Immunology, 2023)
Gliomas account for the majority of brain malignant tumors. As the most malignant subtype of glioma, glioblastoma (GBM) is barely effectively treated by traditional therapies (surgery combined with radiochemotherapy), resulting in poor prognosis. Meanwhile, due to its "cold tumor" phenotype, GBM fails to respond to multiple immunotherapies. As its capacity to prime T cell response, dendritic cells (DCs) are essential to anti-tumor immunity. In recent years, as a therapeutic method, dendritic cell vaccine (DCV) has been immensely developed. However, there have long been obstacles that limit the use of DCV yet to be tackled. As is shown in the following review, the role of DCs in anti-tumor immunity and the inhibitory effects of tumor microenvironment (TME) on DCs are described, the previous clinical trials of DCV in the treatment of GBM are summarized, and the challenges and possible development directions of DCV are analyzed.